The Role of Prenatal Screening in Early Detection of Pregnancy Problems According to Obstetrics and Gynecology Literature - Dwi cFarzani (Indonesian Journal Publisher, 2026)
This study aims to analyze the role of prenatal examination (antenatal care/ANC) in the early detection of pregnancy complications based on recent obstetric and gynecological literature. Using a qualitative descriptive approach through library research, data were collected from peer-reviewed journals, official reports, and relevant academic documents published between 2015 and 2025. The analysis involved thematic identification, data reduction, concept categorization, and inductive synthesis to obtain a comprehensive understanding of prenatal care practices. The findings reveal that structured and systematic prenatal examinations—encompassing community-based education, risk scoring tools such as the Poedji Rochjati Score Card (KSPR), laboratory screening, blood pressure monitoring, biomarker testing, ultrasound, and advanced molecular diagnostics (cfDNA and nanoflower biosensors)—significantly enhance early detection of maternal and fetal complications. Furthermore, family involvement, especially spousal participation and cadre empowerment, strengthens awareness and timely referral for high-risk pregnancies. These results underscore the integration of preventive, technological, and educational dimensions within modern prenatal care. The study concludes that prenatal examination functions as a multilayered system linking biomedical innovation with community engagement, thereby contributing to the reduction of maternal and neonatal morbidity and mortality. The findings provide valuable implications for clinical practice, health education, and policy formulation, while recommending further interdisciplinary research to expand the scope of preventive precision obstetrics.